Evaluation of CD56dim and CD56bright natural killer cells in peripheral blood of women with IVF failures - Farahnaz Mardanian; Moones Kazeroonizadeh; Bahman Rashidi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Infertility is an increasing medical and social problem. In vitro fertilization (IVF) has become a common and accessible treatment for a wide variety of indications that have variable outcomes. Natural killer (NK) cells have been identified as relevant immunological factors involved in reproductive success or failure. Objective: The aim of this study was to compare the percentage of peripheral blood CD56+ (CD56dim and CD56bright) cells and the level of NK cell in patients with IVF failure with those of successful IVF control women. Materials and Methods: We assessed the level of CD56dim CD16+ and CD56bright CD16- cells in 50 women under IVF treatment and compared between successful IVF and IVF failure with the flowcytometry technique. Results: Of studied women, 68% did not response to IVF therapy and 32% had successful IVF, the level of CD56dim CD16+ cells in women with IVF failure was significantly higher than successful IVF (p<0.0001) but the level of CD56bright CD16- cells was not significantly different between women with IVF failure and successful IVF (p=0.28). Conclusion: The results of present study demonstrated that the level of NK cells as a risk factor is associated with pregnancy loss in women with IVF failure. However, number of sample in this study is low and further studies with more sample size are needed to be done. We suggest considering treatment option for women undergoing repeated IVF failure with increased percentage of CD56dim cells and the level of peripheral blood NK cell.